Circular No. 3 of the year 2025 Regarding The Executive Procedures Of The Decree Of The Minister Of Planning, Economic Development And International Cooperation, Head Of The National Wages Council No. (15) of the year 2025 Determining the Minimum Limit Of The Wages Payable To The Workers Of The Private Sector - Ministry of Labor (The Middle East Library For Economic Services, 2025)
On the occasion of the issuance of the decree of the Minister of Planning, Economic Development and International Cooperation, Head of The National Wages Council no. (15) of the year 2025, determining the minimum limit of the wages payable to the workers of the private sector, which stipulated in the first article thereof that “the minimum limit of the wage payable to the workers at the private sector shall be EGP 7000 (Seven Thousand Egyptian Pounds), as of 1/3/2025, calculated on the basis of the wage stipulated in item-c, of article (1) of the labor law”.